Projeto político pedagógico: uma experiência instituinte em São Gonçalo-RJ - Melo, Ruth Ramiro de (2008)
With this research, we tried to recognize why, when and how the actions developed in the process of the construction of Pedagogical Political Project of the Network of Schools of São Gonçalo-RJ (2003-2004), took collective dimensions, making prevail movements where these schools and their teachers increased their autonomy, including, creation and solidarity. Thus, sought is mapping collisions, struggles and creating statements that were happening during the movement that filled the schools in that period, and the limitations, the locks and the contradictions that accompanied them. It took as a reference for theoretical discussions, elaborations of Walter Benjamin, Paulo Freire and Célia Linhares, which improved experiences that do not separate from a multiplicity of voices and feelings produced by the subject in their stories. For this, appealed to the narratives, tool for expression of experience in the process of remembering, seeking the path of women and men as natural events and plurals in experiments that emerged within the meaning of Benjamin, a living memory of the unfinished stories process of teaching. The tapping occurred during the process of discussion of Political Pedagogical Projects in search of dialogical relationship of past demands that claimed the entrelacement of other stories to education of the city, from the own experience of the Network, to recreate collective actions.